Engineered T cells from induced pluripotent stem cells: from research towards clinical implementation - Netsrithong, Ratchapong; Garcia-Perez, Laura; Themeli, Maria (Frontiers in Immunology, 2024)
Induced pluripotent stem cell (iPSC)-derived T (iT) cells represent a groundbreaking frontier in adoptive cell therapies with engineered T cells, poised to overcome pivotal limitations associated with conventional manufacturing methods. iPSCs offer an off-the-shelf source of therapeutic T cells with the potential for infinite expansion and straightforward genetic manipulation to ensure hypoimmunogenicity and introduce specific therapeutic functions, such as antigen specificity through a chimeric antigen receptor (CAR). Importantly, genetic engineering of iPSC offers the benefit of generating fully modified clonal lines that are amenable to rigorous safety assessments. Critical to harnessing the potential of iT cells is the development of a robust and clinically compatible production process. Current protocols for genetic engineering as well as differentiation protocols designed to mirror human hematopoiesis and T cell development, vary in efficiency and often contain noncompliant components, thereby rendering them unsuitable for clinical implementation. This comprehensive review centers on the remarkable progress made over the last decade in generating functional engineered T cells from iPSCs. Emphasis is placed on alignment with good manufacturing practice (GMP) standards, scalability, safety measures and quality controls, which constitute the fundamental prerequisites for clinical application. In conclusion, the focus on iPSC as a source promises standardized, scalable, clinically relevant, and potentially safer production of engineered T cells. This groundbreaking approach holds the potential to extend hope to a broader spectrum of patients and diseases, leading in a new era in adoptive T cell therapy.